Annual report 2007-2010 of the CGIAR System-wide Genetic Resources Programme - Bioversity International; CGIAR Systemwide Genetic Resources Programme (2010)
The report contains the following chapters: Major milestones porior 2007; Programme activities 2007-2010; Futur vision; Memebers of the ICWG-GR 1995-2010; ICWG-GR meetings 1995-2010; SGRP contacts in Bioversity 2010; SGRP reports and publications 2007-2010; Financial report 2007-2010; SGRP donors 1994-2010